المسؤولية المدنية عن أنظمة الذكاء الاصطناعي المستقلة في ظل القانون الإماراتي - Saeed Salem Khalifa Almazrouei; Siti Aisyah Samudin; Mahamatayuding Samah; Hanira Hanafi (Universiti Sains Islam Malaysia, 2026)
The swift rise of the use of autonomous artificial intelligence (AI) has resulted in a major area of uncertainty for law, especially in relation to how to assign civil liability for incidents that are not directly caused by human action. The situation marks a major regulatory gap, since traditional tort law principles—particularly fault and causation—have been developed for making sense of human actions and are still not ready to cope with the autonomous and adaptive behavior of AI. Through a research methodology that is doctrinal and analytical, the paper conducts a comparative study of recent regulatory approaches in Europe and the UK and considers their normative relevance to the legal framework of the UAE. The results reveal that the recognition of AI legal personality does not provide a feasible or protective solution since these systems lack the legal capacity, intent, and independent patrimonial assets needed for effective compensation. Rather, the research advocates for a regulatory model based primarily on human accountability, with the backing of mandatory insurances and compensation funds for high-risk AI applications. Moreover, this research is a valuable contribution to the international legal discussion by presenting the Global South and Middle Eastern viewpoint on the governance of AI liability, including a flexible regulatory framework that not only stimulates technological innovation but also ensures victim protection and legal certainty, and by enhancing the comparative discussion on the future formation of AI civil liability regimes